2020
DOI: 10.1101/2020.06.17.156554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structure of the SARS-CoV-2 3a ion channel in lipid nanodiscs

Abstract: SARS-CoV-2 encodes three putative ion channels: E, 8a, and 3a. In related SARS-CoV-1, 3a is implicated in viral release, inflammasome activation, and cell death and its deletion reduces viral titer and morbidity in animal models, suggesting 3a-targeted therapeutics could treat SARS and COVID-19. However, the structural basis for the function of 3a is unknown. Here, we show that SARS-CoV-2 forms large conductance cation channels and present cryo-EM structures of dimeric and tetrameric SARS-CoV-2 3a in lipid nan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(168 citation statements)
references
References 78 publications
11
154
1
Order By: Relevance
“…However, a recent study showed that the mutation Gln57His does not affect the assembly or functional properties of this putative cation channel (Kern et al, 2020). SARS-CoV-2 N protein, a promising drug target for COVID-19, is a multifunctional RNA-binding protein required for RNA transcription and replication in virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that the mutation Gln57His does not affect the assembly or functional properties of this putative cation channel (Kern et al, 2020). SARS-CoV-2 N protein, a promising drug target for COVID-19, is a multifunctional RNA-binding protein required for RNA transcription and replication in virus.…”
Section: Discussionmentioning
confidence: 99%
“…ORF3a is an accessory protein of 275 amino acids long. It is a transmembrane protein which can exist in dimeric or tetrameric forms, and are shown to have ion channel activity [52][53][54] . While there are 23 new significant mutations emerged in the second phase, 12 mutations that are significant in the first phase are not seen in the second phase.…”
Section: Q57h and G251v Are Prominent In Orf3amentioning
confidence: 99%
“…1.A). All these mutations have been already identified in other studies 8,9,10 , although with different frequencies.…”
Section: Results and Discussion: Mutations Frequency Analysismentioning
confidence: 63%
“…Mutation G25563T produce a Q57H variant of Orf3a (Fig. 7.C) that did not show significant differences in expression, stability, conductance, selectivity or gating behavior 8 . We modelled Q57H mutation and we did not observe differences in the radius of constriction (Fig.…”
Section: G25563tmentioning
confidence: 95%
See 1 more Smart Citation